C1-C4 Dorsal Column Stimulation for Refractory Occipital Neuralgia Treatment. Case Report - Malheiros, José Augusto; Cancado, Sergio Augusto Vieira; Oliveira, Célia Maria de; Santos, Wancler Albert Gomes dos (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Introduction Refractory occipital neuralgia is a difficult medical condition, especially when the patient has already been submitted to occipital nerve neurectomy and radiofrequency rhizotomy. There is no case report of spinal cord stimulation in the C1-C4 cervical segments for this condition.Objective To evaluate if C1-C4 dorsal spinal cord stimulation is effective in a patient with refractory occipital neuralgia who was already submitted to neurectomy and rhizotomy.Methods After obtaining the approval from the Ethics Committee of one of our institutions, a unilateral laminectomy was performed between C3 and C4, and a neurostimulator lead was conducted until the posterior portion of the C1 arc was in full view. Then we performed an intraoperative test to evaluate the correspondence between pain location and stimulation-induced paresthesias. We could not put the subcutaneous lead for such condition because of the scar tissue of the area and the previous neurectomy.Results After one year of follow up, we noticed a dramatic improvement in pain control, as well as medication withdrawal. The score of the visual analogue scale was 9 before the surgery, and it dropped to 2 after 1 year of follow-up.Conclusion Spinal cord stimulation between the C1 and C4 cervical segments can be an option for selected cases of refractory occipital neuralgia, including those patients who have already been submitted to neurectomy or rhizotomy.
Keywords: occipital neuralgia; neurostimulation; spinal cord stimulation; case report